8+2y-3=9y+5-6y

Simple and best practice solution for 8+2y-3=9y+5-6y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8+2y-3=9y+5-6y equation:


Simplifying
8 + 2y + -3 = 9y + 5 + -6y

Reorder the terms:
8 + -3 + 2y = 9y + 5 + -6y

Combine like terms: 8 + -3 = 5
5 + 2y = 9y + 5 + -6y

Reorder the terms:
5 + 2y = 5 + 9y + -6y

Combine like terms: 9y + -6y = 3y
5 + 2y = 5 + 3y

Add '-5' to each side of the equation.
5 + -5 + 2y = 5 + -5 + 3y

Combine like terms: 5 + -5 = 0
0 + 2y = 5 + -5 + 3y
2y = 5 + -5 + 3y

Combine like terms: 5 + -5 = 0
2y = 0 + 3y
2y = 3y

Solving
2y = 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.
2y + -3y = 3y + -3y

Combine like terms: 2y + -3y = -1y
-1y = 3y + -3y

Combine like terms: 3y + -3y = 0
-1y = 0

Divide each side by '-1'.
y = 0

Simplifying
y = 0

See similar equations:

| v/2-13=4 | | 30÷z=6 | | -5.8-4y=16 | | 2r+5r=28 | | 12x+2[6+7(x+1)]=0 | | (-14/3)*(-13/69)= | | 108-6x=12x+24 | | -14/3*(-13/69)= | | -(6y+2)-(-5y-3)=-7 | | -14/3*-13/69= | | 12=2u-8 | | 9w^2+30wt+25t^2= | | 2x-.8-.2x=2.8 | | -9.2x=82.8 | | X^4-12X^2+24X-14=0 | | 3y=-29 | | 2m+10=4m+2 | | 5lne^2=x | | x^2-90x-1000=0 | | 16=18x-12 | | 4a-6=5+6a | | -6x-5+7x=-7+7 | | 3x+.25x=26 | | 5.1q-3.8-4.7q=0.6q-5.3 | | 9x+6=8x+2 | | 5y-3+y+27=7y+30-3y | | -5x+3+3x=-6x-9 | | 6x^2+4=16+4x^2 | | -1-4=5t | | 5(-2x-4)-3x=-9x | | x+7y=3 | | 3-4(3x+2)=7-(9x-1) |

Equations solver categories